2018
DOI: 10.1007/s10853-018-2551-6
|View full text |Cite
|
Sign up to set email alerts
|

A general perspective of Fe–Mn–Al–C steels

Abstract: During the last years, the scientific and industrial community have focused on the astonishing properties of Fe-Mn-Al-C steels. These high advanced steels allow high-density reductions about ~18% lighter than conventional steels, high corrosion resistance, high strength (ultimate tensile strength (UTS) ~1 Gpa) and at the same time ductility above 60%.The increase of the tensile or yield strength and the ductility at the same time is almost a special feature of this kind of new steels, which makes them so inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(43 citation statements)
references
References 375 publications
(459 reference statements)
0
42
0
1
Order By: Relevance
“…The dependency of the elements Mn, Al, Si and C on the SFE can be found here [ 26 ]. Besides the chemical composition, the SFE depends on the microsegregation (Suzuki effect) temperature and the grain size [ 27 ]. Since medium manganese steels exhibit a complex microstructure, these aforementioned effects can be controlled by the amount and the stability of metastable retained austenite (RA), which can be adjusted via a heat treatment process of intercritical annealing [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dependency of the elements Mn, Al, Si and C on the SFE can be found here [ 26 ]. Besides the chemical composition, the SFE depends on the microsegregation (Suzuki effect) temperature and the grain size [ 27 ]. Since medium manganese steels exhibit a complex microstructure, these aforementioned effects can be controlled by the amount and the stability of metastable retained austenite (RA), which can be adjusted via a heat treatment process of intercritical annealing [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hwang et al suggested that twinning-induced plasticity (TWIP) steel is a promising material for high strength wire rod products 13,14) including flat-rolled wire applications 15) because TWIP steels meet the strict property requirements for wire rod products originating from their outstanding combination of strength and ductility. [16][17][18][19][20][21][22][23][24] Moreover, TWIP steels have a higher resistance to hydrogen-delayed fracture in comparison with conventional plain carbon steels that are typically used for wire rod applica-tions. This is mainly due to the face-centered cubic (FCC) structure of TWIP steel.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-Mn-Al-C steels allow high-density reduction about ∼ 18 % lighter than conventional steels, high corrosion resistance, high strength (ultimate tensile strength ∼ 1 GPa), and at the same time ductility above 60 % [1], which have many potential applications in the field of advanced transportation systems, wear parts, shape memory alloys, and biomaterials, especially in automotive and powertrain systems. This has caused great interest in the automotive armor, mining, and steel industries.…”
Section: Introductionmentioning
confidence: 99%